Homeschooling as an Alternative for Children's Moral Development in the Era of Digital Disruption and Moral Degradation - Pawestri, Rurin Ratna; Ishaq, M.; Purnamasari, Ica (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
This article examines homeschooling as an alternative model of moral education for children in the midst of the digital disruption era and moral degradation. The rapid development of digital technology has significantly influenced children’s behavior, communication, and moral values. Traditional schools often struggle to provide a balanced response to these challenges, while homeschooling offers a more personal and value-based approach. This study employs a qualitative literature review by analyzing relevant journals, books, and reports from both national and international sources. The findings reveal that homeschooling not only strengthens academic knowledge but also fosters moral resilience, character formation, and parental involvement as the primary agents of education. This study contributes to the discourse on appropriate educational alternatives to address moral decline in the digital.